2017
DOI: 10.3389/fmicb.2017.00836
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Communities in Boreal Forest Mushrooms Are Shaped Both by Soil Parameters and Host Identity

Abstract: Despite recent advances in understanding the microbiome of eukaryotes, little is known about microbial communities in fungi. Here we investigate the structure of bacterial communities in mushrooms, including common edible ones, with respect to biotic and abiotic factors in the boreal forest. Using a combination of culture-based and Illumina high-throughput sequencing, we characterized the bacterial communities in fruitbodies of fungi from eight genera spanning four orders of the class Agaricomycetes (Basidiomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
87
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(95 citation statements)
references
References 79 publications
7
87
0
1
Order By: Relevance
“…In terms of bacteria identified based on 16S sequences, the main clades found were consistent with those reported by Pent et al. () as being common among boreal forest mushrooms. That the method yielded reliable, repeatable data on bacterial community structure was also confirmed by the general similarity of communities among the two 16S PCR replicate data sets (Supporting Information Figures and ).…”
Section: Discussionsupporting
confidence: 89%
“…In terms of bacteria identified based on 16S sequences, the main clades found were consistent with those reported by Pent et al. () as being common among boreal forest mushrooms. That the method yielded reliable, repeatable data on bacterial community structure was also confirmed by the general similarity of communities among the two 16S PCR replicate data sets (Supporting Information Figures and ).…”
Section: Discussionsupporting
confidence: 89%
“…According to results reported by Pent and colleagues (), the composition of the bacterial populations inhabiting fungal fruiting bodies is strongly conditioned by fungal identity, suggesting that some bacteria may have specific symbiotic functions in different groups of mushrooms. The characterization through high‐throughput community sequencing of the microbiome of edible mushrooms picked from the wild reinforces the hypothesis that the interactions between microbial communities and mushrooms are related to morphological changes during fruiting body development (Zhou et al ., ).…”
Section: The Mushroom Holobiont: Mycelium and Fruit Bodymentioning
confidence: 82%
“…There is also evidence that the relative abundance of Proteobacteria is higher in the mycosphere (Warmink et al ., ) and ectomycorhizosphere (Uroz et al ., ; Antony‐Babu et al ., 2013) compared to the surrounding soil, suggesting the tendency of Proteobacteria for colonizing fungus‐related habitats. A high relative abundance of Bacteroidetes, the second‐largest bacterial phylum in I. terrigena , is also often found in ectomycorhizosphere, mycosphere and fruiting‐bodies of ascomycetous as well as basidiomycetous fungi (Uroz et al ., ; Antony‐Babu et al ., 2013; Benucci and Bonito, ; Halsey et al ., ; Pent et al ., ). In particular, the relative abundance of Sphingobacteria in I. terrigena was similar to that in Elaphomyces granulatus (Quandt et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…S3). Similarly to our study, Proteobacteria has been identified as a very common bacterial group in several ascomycetous (Barbieri et al ., ; Quandt et al ., ; Benucci and Bonito, ) as well as basidiomycetous (Kumari et al ., ; Pent et al ., ) fruiting‐bodies. There is also evidence that the relative abundance of Proteobacteria is higher in the mycosphere (Warmink et al ., ) and ectomycorhizosphere (Uroz et al ., ; Antony‐Babu et al ., 2013) compared to the surrounding soil, suggesting the tendency of Proteobacteria for colonizing fungus‐related habitats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation